BS38 Role of neutrophil elastase in abdominal aortic aneurysms and thoracic aortic dissection. (May 2019) - Pearce, Stuart; Xiao, Qingzhong; Wu, Wei; An, WeiWei; Yang, Mei
Abstract : Abdominal Aortic Aneurysm (AAA) affects 4–5% of men over 65, and Thoracic Aortic Dissection (TAD) is a life-threatening aortic pathology where 75% of patients die within 2-weeks post-onset. Relatively little is known about the underlying mechanisms, which warrants further investigation. Neutrophil Elastase (NE) is an enzyme with roles in priming of the immune system, clearance of large pathogens and remodelling of extra-cellular-matrix proteins, all influential in AAA and TAD. Our recent study suggests a causal role for NE in hyperlipidemia-induced atherosclerosis. However, little is known regarding implications of NE in AAA and TAD. This Study aims to investigate the role of NE within both pathologies. Gene-expression of NE and AAA-associated markers, MMP-2 and MMP-9, were significantly up-regulated by CaCl2-and AngII-treatment in the cultured vascular smooth muscle cells, endothelial cells and macrophages. In both AngII- and CaCl2-induced AAA mouse models, reduction of aortic expansion in NE-knockout mice was observed, compared with wild-type littermates. TAD experiments reaffirmed the functional importance of NE, with significant reduction in death within NE-knockout mice. Histological and Proteomics analysis was carried out in order to determine changes produced by loss of the NE gene within these models. Preliminary translational work is underway, with an Audit of Aneurysm patients' blood profiles. Additionally, peripheral blood and aortic tissues were harvested from surgical repair patients with AAA for NE expression analysis. Initial results show an alteration in proportions of White Blood cell populations, namely macrophages and lymphocytes within expansive aneurysms and co-localisation of NE with MMPs in AAA human samples. This study suggests NE could be a regulator of aortic expansion and dissection, and therefore a potential target for AAA and TAD treatment. Further work is still needed to elucidate the causal mechanism by which NE takes its effect on AAA and TAD. Conflict of interest: no